Seaports Administration in Nigeria: A Study of Apapa Port Complex - Ifeanyi, Eleagu, Greene; Joseph, Akonye, Enyioma (European Scientific Journal, ESJ, 2018)
The administration of the seaports in Nigeria rests solely on the Nigeria Ports Authority (NPA). This means that, the Port Authority plays an important role in the economic and trade development of Nigeria. Nigeria Ports Authority operates under the supervision of the Federal Ministry of Transport with the responsibility of providing specific ports and harbour services for the country’s maritime industry. Presently, Nigerian Ports Authority controls eight (8) major ports excluding oil terminals with a cargo handling capacity of about 35 million tons per annum. However, this paper examined Nigeria ports authority in the effective and efficient port administration in Nigeria, using Apapa port complex as a case study. The paper also examined the role of port worker in achieving the Federal Government objectives in the establishment of sea ports in Nigeria. The paper equally looked at the developmental process of sea ports in Nigeria, as well as the reasons/need for the establishment of sea ports in Nigeria. The paper by extension looked at the setbacks faced by the Nigeria seaports in general and Apapa port in particular since its establishment. The general system theory was used as our theoretical framework of analysis. Based on the poor conditions and inadequate state of equipment at the port, the paper suggests that the Apapa port management in particular and the management of other sea ports in general should facilitate the procurement and maintenance of the functional equipment in the ports to enhance speedy cargo handling. In addition, more warehouses/storage facilities should be built to accommodate incoming and outgoing goods and services therein, among others.